Perbedaan Kemandirian Remaja Berdasarkan Status Pekerjaan Ibu - Khotimah, Khusnul (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2015)
This research aims to understand the difference in the autonomy of adolescent having the working mother and non working mother on a student XI is social class in high school land 103 east jakarta. Research is conducted during the 12 months since january to december 201 Research method used is a method of survey with comparative approach .The population in this research is a student XI route social class in high school land of 103 east jakarta. The sample collection technique used is non probability sampling with saturated sampling techniques. The sample is a total of 116 students consisting of 32 students male having a working mother , 28 a female student who has mom worked , 26 students male having a mother does not work and 30 female students having mother does not work . The aspect of the autonomy of views based on emotional autonomy , the autonomy of mannerisms and autonomy of the value of. The results show normality test data the autonomy of adolescent boys and women who possess the mother worked and autonomy of adolescent boys and women who possess the mother does not work berdistribusi normal and homogeneity test data showed berdistribusi homogeneous. The results of testing the hypothesis of statistics using anova one direction obtained Fhitung = 19 the first mistake 0.05 so that we can conclude that there were differences autonomy of adolescentÂ  having the work and not working. Especially the manner of differences of treatment that causes the autonomy of the mother parents especially between men and women is different. Adolescent boys autonomy more given the opportunity in the development is given the exercise of independence as given the opportunity and freedom of running their activities without relying on parents especially mothers , but not in spite of supervision that parents especially mothers with adolescent boys develop good along with increasing autonomy the ability and experience that he got various.